Transcriptome Analysis of the Liver and Muscle Tissues of Dorper and Small-Tailed Han Sheep - Peng, Hongyang; Hu, Mingyue; Liu, Zhengxi; Lai, Weining; Shi, Lulu; Zhao, Zhongli; Ma, Huihai; Li, Yumei; Yan, Shouqing (Frontiers in Genetics, 2022)
It is well known that Dorper (DP) is a full-bodied, fast-growing and high dressing percentage breed, while the production performance of Small-tailed Han sheep (STH) is not so excellent, in contrast to DP. Therefore, in this study, a comparative transcriptomic analysis of liver and muscle tissues from DP and STH breeds was carried out to find differentially expressed genes (DEGs) that affect their growth and meat quality traits. The results showed that the total number of DEGs was 2188 in the two tissues. There were 950, 160 up-regulated and 1007, 71 down-regulated genes in the liver and muscle, respectively. Several DEGs such as TGFB1, TGFB3, FABP3, LPL may be associated with growth and development in DP. Also, several GO terms were found to be associated with muscle growth and development, such as developmental growth (GO:0048589), and myofibril (GO:0030016). Further validation of 8 genes (6 up-regulated, and 2 down-regulated) was performed using quantitative RT-PCR. These findings will provide valuable information for studying growth and development as well as meat quality traits in sheep.